Teaching for an Inclusive, Technologically Competent and Sustainable Society: Book of Abstracts (University of Maribor Press, 2024)
This conference proceeding, titled "Rethinking Childhood III – Teaching for an Inclusive, Technologically Competent, and Towards Sustainability Oriented Society," encapsulates 39 research contributions that collectively aim to advance educational practices. The studies presented address a variety of themes including inclusive education, the integration of technology in teaching, and promoting sustainability through educational initiatives. The research spans diverse methodologies and educational levels, from preschool to higher education, highlighting innovative approaches to curriculum development, digital literacy, and competency-based learning. Key findings demonstrate the importance of fostering an inclusive environment, utilizing digital tools effectively, and encouraging sustainable practices within educational settings. This compilation of contributions provides valuable insights for educators, policymakers, and researchers dedicated to evolving educational frameworks to meet the demands of a modern, interconnected, and sustainable society.